Effect of microencapsulated process on stability of mulberry polyphenol and oxidation property of dried minced pork slices during heat processing and storage. (February 2019) - Xu, Liang; Cheng, Jing-Rong; Liu, Xue-Ming; Zhu, Ming-Jun
Abstract: Microencapsulation is a promising technique for improving the stability of bioactive compounds. This study is to evaluate the effect of mulberry polyphenols microcapsules (MPM) as a partial substitute of mulberry polyphenol (MP) in mitigating of polyphenols degradation and oxidation of dried minced pork slice. Results presented that stability of MP is remarkable enhanced when it was microencapsulated using gum Arabic and the optimum core/wall ratio was 1/90. Partial replacement of MP by MPM as antioxidant in slices can effectively enhance polyphenols stability while exhibit synergistic inhibitory effect on protein and lipid oxidation. After 20 days storage, about 50.63% phenolic, 37.95% flavonoid and 51.32% anthocyanin were recovered in slices made with both MPM and MP, and the slices showed the best oxidation stability among all tests and good color stability. All these results demonstrated that mulberry polyphenol may be substituted for chemical antioxidants for meat products by microencapsulation technology. Highlights: Microencapsulation enhances polyphenols stability of dried minced pork slices. Mulberry polyphenol and its microcapsule show synergistic effect on retarding slice oxidation. Microencapsulation improves color stability of dried minced pork slices.